A - Ahmad, Nihal (Oxford University Press, 2005)
This book is the first authentic book on the history of Radio Pakistan/PBC. It is a vehicle for ventilation of aspirations and grievances, leading, directing and mobilising the nation towards set goals. The detailed and comprehensive information provided by this reference work covers all facts of Radio Pakistan that can be resourceful. It emphasizes the role that radio can play as an instrument of change, as a trend-setter and a development support communication system